Pola Pemilihan Kepala Daerah Asimetris: Studi Evaluatif Pemerintahan Daerah (Asymmetric Regional Head Election Patterns: An Evaluative Study of Regional Government) - Zakia Azzahro, Umi; Maya Oktavia, Enika; Zahra, Siti; Ahmad Fahrizi, Irgi; Basid Fuadi, Abdul (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2023)
The uniformity of the regional head election (Pilkada) model in Indonesia, which employs a direct election system, has given rise to various problems. These issues range from conflicts between supporters of candidate pairs, APBD deficits to fund regional elections, to vertical government disharmony. However, Article 18, paragraph (4) of the 1945 Constitution of the Republic of Indonesia, which uses the phrase “democratically elected,” allows for various election methods other than direct elections. This is conceptualized as asymmetric regional elections. This paper aims to formulate alternatives for implementing regional elections asymmetrically, addressing problems in the following forms: (1) the relevance of asymmetric regional elections in realizing the effectiveness of regionalgovernment; (2) the concept of implementing asymmetric regional elections; and (3) indicators that can be used in the implementation of Asymmetric Regional Elections. The paper employs doctrinal legal research methods with both a statutory and conceptual approach. The main finding is that regional elections can be carried out asymmetrically, using indicators related to democratic maturity and the financial capacity of each region. As a result, regional elections can be conducted in three ways: direct elections, elections through the DPRD, and elections within the executive. AbstrakPenyeragaman model pemilihan kepala daerah (pilkada) di Indonesia menggunakan sistem pemilihan secara langsung telah menimbulkan berbagai permasalahan. Mulai dari konflik antara pendukung pasangan calon, defisit APBD untuk mendanai pilkada, hingga disharmoni pemerintahan secara vertikal. Padahal konstruksi Pasal 18 ayat (4) UUD NRI 1945 yang menggunakan frasa “dipilih secara demokratis” memberikan ruang bagi beragam metode pemilihan selain pemilihan langsung yang dikonseptualisasikan sebagai pilkada asimetris. Tulisan ini bertujuan merumuskan alternatif pelaksanaan pilkada secara asimetris dengan permasalahan berupa: (1) relevansi Pilkada Asimetris untuk mewujudkan efektivitas pemerintahan daerah; (2) konsep pelaksanaan Pilkada Asimetris; (3) indikator yang dapat digunakan dalam pelaksanaan Pilkada Asimetris. Tulisan menggunakan metode penelitian hukum doktrinal dengan pendekatan perundang-undangan dan pendekatan konseptual. Temuan utama adalah pelaksanaan pilkada dapat dilakukan secara asimetris, dengan menggunakan indikator berupa kematangan demokrasi dan kemampuan finansial masing-masing daerah. Akibatnya, pilkada dapat dilakukan dengan tiga cara: yaitu pemilihan langsung, pemilihan melalui DPRD, dan pemilihan dalam lingkup eksekutif.